Analysis of Difficulties in Learning Tathbiq Hiwar at Senior High School - Mugi Rahayu Nur; Nunung Nursyamsiah; Hikmah Maulani (Pusat Studi Bahasa dan Publikasi Ilmiah, 2023)
This study aims to identify difficulties and factors experienced by tenth-grade students and educators in implementing hiwar (dialogue) learning in a Senior High School located in Bandung City. The research used a descriptive method with a qualitative approach. Techniques of data collection through test and non-test instruments. The test instrument is conducted through Arabic dialogue and non-tests through observation, questionnaires, and interviews. Data analysis techniques are carried out by reducing data, presenting data, and drawing conclusions from existing data. The results of the study revealed the difficulties encountered in hiwar learning are students feel incapable of understanding the hiwar learning materials provided by the teacher, students can not pronounce Arabic words, and can not express intonations correctly in Arabic dialogue. The difficulty factors are educational backgrounds, methods of learning, learning media, student ignorance of Arabic speech along with intonation, do not have textbooks and limited time, lack of student interest and motivation in learning hiwar, and student self-confidence.